High Temperature Behavior of Yttrium – Doped Siliconized 316L Stainless Steel at CO2 Environment - Mohammed Hussein, Rajab (Anbar Journal of Engineering Sciences, 2009)
In this study, silicon and yttrium were simultaneously co-deposited by diffusion into austenitic stainless steel (AISI 316L) substrates, by a single-step pack cementation process. Cyclic oxidation tests were conducted on the siliconized coating and on the yttrium doped siliconized coating of stainless steel in CO2 atmospheric pressure at temperatures 800° C and 900° C for 100h at 10h cyclic. The results show that the initial weight gain is rapid and increased as the temperature increased. The oxidation resistance of the yttrium doped siliconized of stainless steels was significantly improved as compared with the siliconized stainless steels. The scale formed on coated stainless steel after oxidation in CO2 environment was thick and consisted of Y2O3, SiO2, Fe2O3 and chromium oxide. Optical metallography (LOM) and X-ray diffraction (XRD) were used to characterize the resulting coating and cyclic oxidation structures.